Efficiency of Public Education Expenditure in India: A Stochastic Frontier Analysis of State-Level Secondary School Completion - Sinha, Jitendra Kumar (Journal of Behavioral Economics and Policy, 2025)
Public expenditure on education plays a crucial role in promoting human capital formation and long-term economic development. In decentralized fiscal systems such as India, state governments bear primary responsibility for financing and delivering educational services. However, variations in fiscal capacity, governance structures, and socio-economic conditions may result in significant differences in the efficiency with which educational resources are utilized. This study evaluates the efficiency of public education expenditure across Indian states using a stochastic frontier analysis (SFA) framework based on panel data for the period 2014–2023, with secondary school completion rate as the primary outcome variable. The empirical model estimates the relationship between educational outcomes and key determinants, including government education expenditure, economic development, poverty incidence, and population growth. The results indicate that public education spending exerts a positive and statistically significant effect on secondary school completion, while poverty remains a major constraint on educational attainment. The estimated technical efficiency scores range from 0.68 to 0.93, with a mean of approximately 0.82, indicating substantial inter-state disparities in the utilization of public education resources. Furthermore, the estimated gamma (γ) value of 0.712 suggests that a large proportion of the variation in educational outcomes is attributable to inefficiency rather than random shocks. Robustness checks using Data Envelopment Analysis confirm the overall pattern of efficiency differentials across states. The findings highlight that improvements in educational outcomes depend not only on increased fiscal allocations but also on more effective governance and institutional capacity in managing educational resources. The study concludes with policy recommendations aimed at strengthening the efficiency and equity of public education spending in India.